Implementasi Astagga Yoga Sebagai Penguatan Pendidikan Karakter di SMP Nasional Denpasar - I Komang Jhon Purnawan (Jurnal Yoga dan Kesehatan, 2018)
The education of character’s building is a rising brand new innovation to incrase moral degradation who arefacing by teenagers now adays. Spiritual and mental adding value are very necessary to support the processof character’s building education. The education process which concentrates in its spiritual and mentalityhas been found in the concept of Hinduism called the teachings of Yoga Specifically, it is about concept Astangga Yoga such as: yama=control, nyama=morality, asana=body posture, pranayama=breathe management, pratyahara=sensual with drawal, dharana=attention, dhyana=meditation, sadism=concentration.At Denpasar Nasional Middle School, they have carried out the teaching process of Astangga yoga as areinforcement of character education. The existence of ekstrakulikular Yoga as a stage of phsycal trainingfor student/student and the process of concentration and control of emotions (emotions), has been carriedout at the beginning of the learning process in the classroom during the study of Hinduism dab Manners.